Toward the synthesis of incargranine B and seneciobipyrrolidine. Synthesis of octahydro‐dipyrroloquinoline skeleton via dipolar cycloaddition/amination sequence. (26th May 2021) - Simic, Milena; Jovanovic, Predrag; Petkovic, Milos; Tasic, Gordana; Jovanovic, Milos; Savic, Vladimir
Abstract: Octahydro‐dipyrroloquinoline skeleton is the building component of a very few naturally occurring compounds. Nevertheless, these natural products have been attractive synthetic targets, and their study commanded development of efficient synthesis of this core. While the reported methods are based on the dimerization procedure of N‐arylpyrrolidines of N‐arylhomopropargyl amines, our approach relay on dipolar cycloaddition/amination sequence. This strategic approach allows sequential introduction of aromatic moieties increasing the product diversity and hence may be useful in further exploration of incargranine B or seneciobipyrrolidine derivatives. Abstract :